Oxidative Carbon-Carbon Bond Formation via Allyldimethylsilyl Enol Ethers - Konkol, Leah C.; Jones, Brian T.; Thomson, Regan J. (Organic letters, 2009)
A method for the oxidative alkylation of ketones through intramolecular allyl-group transfer within preformed allyldimethylsilyl enol ethers Is reported. A number of examples are detailed, including a study into the effects of resident sterocenters within cyclic enol ethers.